Neglected Elderly: Lacking Welfare Policies in Indonesian Local Governments - Said Fitra Akbar; Rifqi Ridlo Phahlevy (Rechtsidee, 2021)
This study aimed to examine the social welfare policies for elderly citizens in local government in Indonesia, with a particular focus on the existence of regional regulations that address the needs of this vulnerable population. A normative method was employed, utilizing a statutory approach and deductive analysis of legal materials. The results of the study indicate that not all regions in Indonesia have local regulations that specifically address the welfare of the elderly. This finding highlights the need for increased attention and action from local governments in order to ensure the well-being and protection of elderly citizens. Highlights: The study focused on social welfare policies for the elderly in local government in Indonesia. The research revealed that not all regions in Indonesia have local regulations that specifically address the welfare of the elderly. This highlights the need for increased attention and action from local governments to ensure the well-being and protection of elderly citizens.